Artificial immune system for abnormal stock trading detection [electronic resource] - 452181 Ling, Liu Inn (Skudai : Universiti Teknologi Malaysia, 2007)
Thesis (Sarjana Sains (Sains Komputer)) - Universiti Teknologi Malaysia, 2007